The Impact of Quranic Recitations on Grammar and Semantics in the Recitation of Ibn Kathir - Atotileto, Abdussalam Aminu (IJAS: Indonesian Journal of Arabic Studies, 2025)
Purpose— This study aims to explore the grammatical and semantic impact of Quranic readings, focusing on the recitation of Ibn Kathir. It seeks to understand how variant readings contribute to syntactic interpretation and meaning construction within the Quranic text. Design/methods/approach—The research employs a descriptive, inductive, and analytical approach, drawing on examples from the ten canonical qirā’āt. It investigates how early grammarians engaged with Quranic variants, and how these readings shaped syntactic rules and interpretative frameworks. Specific examples from Ibn Kathir’s recitation are examined to highlight grammatical diversity and semantic richness. Findings—The study finds that Quranic readings influence grammatical structure and meaning without generating contradiction. Readings such as those of Ibn Kathir contribute to the flexibility of Arabic syntax and provide insight into semantic nuance. The research also reveals that grammar rules often conform to readings rather than readings being bound by fixed grammatical rules. Research Implications— This study reinforces the importance of Quranic recitation as a source for linguistic evidence and grammatical theory. It contributes to the broader field of Arabic linguistics by demonstrating how qirā’āt function not only as liturgical tradition but also as dynamic linguistic data influencing syntax and semantics across historical contexts.